Quaternary Ideograms as a Didactic Technique to Form Mathematical Conceptual Relationships in University Students - Martínez-Zocón, Raúl Narciso; Esquivel-Grados, José Theódulo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of the study was to establish the degree of influence of quaternary ideograms as a didactic technique in the formation of mathematical conceptual relationships in university students. The data were collected with validated tests to contrast the statistical hypotheses of mean difference with the z statistic in a quasi-experimental design with pre- and post-test, and control group. It was concluded that the use of quaternary ideograms significantly influences the formation of conceptual relationships, considering a confidence level of 95%, which indicates that the didactic technique promotes the development of mathematical conceptual skills from a constructivist perspective.